A longitudinal examination of intellectual capital disclosures and corporate governance attributes in Malaysia - Ahmed Haji, Abdifatah; Mohd Ghazali, Nazli Anum (Emerald Group Publishing Limited, 2013)
Purpose – The purpose of this study is to examine the relationship between intellectual capital disclosure (ICD) and corporate governance attributes following the revised code on corporate governance in Malaysia in 2007. Design/methodology/approach – The sample of the present study was drawn from top companies listed on Bursa Malaysia based on their market capitalization for the years 2008, 2009 and 2010. A self-constructed disclosure index was used to assess the extent and quality of ICDs. The panel data regression analysis was employed to examine the relationship between ICDs and corporate governance. Findings – The results revealed that all corporate governance attributes namely board size, independent directors, board effectiveness and position of the chairman (except family members on the board) were significant in explaining the extent and quality of ICDs in the expected direction. Director ownership was found to be consistent in negatively relating to both the extent and quality of ICDs. Government ownership was marginally significant in determining the extent of ICDs. Practical implications – The findings suggest that the revised corporate governance code has a positive impact on ICD at least in the case of large Malaysian listed companies. This implies that regulatory efforts in enhancing corporate governance in Malaysia is starting to prove fruitful in encouraging companies to be involved in more IC investment and hence disclosure. Originality/value – This paper is one of the few studies which investigate the influence of corporate governance on ICDs longitudinally in a developing country following revision to the corporate governance code in Malaysia in 2007. Keywords Intellectual capital disclosure, Corporate governance, Ownership structure, Annual reports, Malaysia